ANALYSIS OF THE IMPLEMENTATION OF TAX INCENTIVES IN THE FORM OF TAX ALLOWANCE AND TAX HOLIDAY IN INDONESIA COMPARED TO THAILAND - Stefanus Tevrianto Temanta Surbakti; Elisa Tjondro; Wiyono Pontjoharyo (Jurnal Ekonomi, 2023)
This study aims to determine the various differences between the application of tax incentives in the form of tax allowances and tax holidays in Indonesia and the application of tax incentives in Thailand, with an emphasis on evaluating the application of tax incentives and tax allowances in Indonesia. Researchers used qualitative research methods with a comparative descriptive qualitative design. This study uses two types of data sources, namely primary data and secondary data. Primary data is in the form of interviews with tax practitioners, tax officials, and companies that receive tax incentives. Then secondary data in the form of data from books, laws, and other regulations that lead to tax allowances and tax holidays. Researchers used data collection instruments in the form of a list of interview guidelines and notes on the results of the interviews. The results of this study indicate that the application of tax incentives in Indonesia in terms of processing time and usage is better than that in Thailand. As for the facilities, bureaucracy, application process, investment status, and the facilities provided in Thailand are better. The researcher also made comparisons based on infrastructure, socio-political, and population density factors, and found that these factors sufficiently influence investors to determine investment destination countries. In addition, the researchers also found that there are several conditions for submitting tax incentives that are quite burdensome for business people